2005
DOI: 10.1111/j.1600-079x.2005.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical demonstration of day/night changes of clock gene protein levels in the murine adrenal gland: differences between melatonin‐proficient (C3H) and melatonin‐deficient (C57BL) mice

Abstract: The circadian system comprises several peripheral oscillators and a central rhythm generator that, in mammals, is located in the suprachiasmatic nucleus of the hypothalamus. Expression of clock genes is a characteristic feature of the central rhythm generator and the peripheral oscillators. With regard to the rhythmic production of glucocorticoids, the adrenal gland can be considered as peripheral oscillator, but little is known about clock gene expression in this tissue. Therefore, the present study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 43 publications
3
50
0
1
Order By: Relevance
“…In the human, metabolic clearance of cortisol is higher in the early morning than in the evening [de Lacerda et al, 1973;Plat et al, 1999], therefore the circadian changes in plasma cortisol and in the response to ACTH in the capuchin monkey, most likely originate at the adrenal cortex level. The underlying mechanisms helping to explain our results may involve: (i) circadian changes in the activity and/or expression level of steroidogenic enzymes, shown in rhesus monkey (Macaca mulatta) for 17a-hydroxylase-17-20 lyase and cholesterol side chain cleavage [Lemos et al, 2006]; (ii) clock gene expression as shown in mouse and rhesus monkey adult adrenal [Lemos et al, 2006;Oster et al, 2006;Torres-Farfan et al, 2006a] and adult and fetal capuchin monkey adrenal [Torres-Farfan et al, 2006b;Valenzuela et al, 2005]; and/or (iii) circadian changes in adrenal sensitivity to ACTH mediated by adrenal innervation as described in the rat [UlrichLai et al, 2006]. Clearly, it is necessary to dissect how these overlapping mechanisms contribute to circadian adrenal cortex function.…”
Section: Discussionmentioning
confidence: 90%
“…In the human, metabolic clearance of cortisol is higher in the early morning than in the evening [de Lacerda et al, 1973;Plat et al, 1999], therefore the circadian changes in plasma cortisol and in the response to ACTH in the capuchin monkey, most likely originate at the adrenal cortex level. The underlying mechanisms helping to explain our results may involve: (i) circadian changes in the activity and/or expression level of steroidogenic enzymes, shown in rhesus monkey (Macaca mulatta) for 17a-hydroxylase-17-20 lyase and cholesterol side chain cleavage [Lemos et al, 2006]; (ii) clock gene expression as shown in mouse and rhesus monkey adult adrenal [Lemos et al, 2006;Oster et al, 2006;Torres-Farfan et al, 2006a] and adult and fetal capuchin monkey adrenal [Torres-Farfan et al, 2006b;Valenzuela et al, 2005]; and/or (iii) circadian changes in adrenal sensitivity to ACTH mediated by adrenal innervation as described in the rat [UlrichLai et al, 2006]. Clearly, it is necessary to dissect how these overlapping mechanisms contribute to circadian adrenal cortex function.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, in the capuchin, the fetal SCN and the fetal adrenal show circadian oscillation of two clock genes and evidence of oscillatory function downstream of these genes. Recently, several authors reported the oscillatory expression of clock genes in the adrenal gland of adult rodents (Ishida et al, 2005;Watanabe et al, 2006;Torres-Farfan et al, 2006b) and primate (Lemos et al, 2006), providing strong evidence for the presence of a peripheral clock in this tissue. This possibility is highly relevant, in light of evidence supporting a role for plasma glucocorticoids in the entrainment of other oscillators (Balsalobre et al, 2000), as well as in control of metabolic rhythms in other organs such as liver (Oishi et al, 2005) and adipocytes (AlonsoVale et al, 2005).…”
Section: The Circadian System and Circadian Clocks Throughout Developmentioning
confidence: 97%
“…Ironically, however, BMAL1 protein levels reach a trough when BMAL1 is displaying the greatest transcriptional activity and peak during the transcription inhibition phase in diverse tissues and cells, including the SCN (23,41,43) (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%